2023
DOI: 10.1101/2023.04.23.537997
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Codon affinity in mitochondrial DNA shapes evolutionary and somatic fitness

Abstract: Somatic variation contributes to biological heterogeneity by modulating cellular proclivity to differentiate, expand, adapt, or die. While large-scale sequencing efforts have revealed the foundational role of somatic variants to drive human tumor evolution, our understanding of the contribution of mutations to modulate cellular fitness in non-malignant contexts remains understudied. Here, we identify a mosaic synonymous variant (m.7076A>G) in the mitochondrial DNA (mtDNA) encoded cytochrome c-oxidase subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…To reconstruct the mutational spectrum for CytB, we made the assumption that all synonymous variants in chordate mitochondrial genomes are possibly neutral. Although potential non neutrality has not been conclusively proven 10 we conducted limited testing to assess the impact of eliminating highly-constrained synonymous positions. Preliminary results indicated that their exclusion did not significantly alter the outcomes (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…To reconstruct the mutational spectrum for CytB, we made the assumption that all synonymous variants in chordate mitochondrial genomes are possibly neutral. Although potential non neutrality has not been conclusively proven 10 we conducted limited testing to assess the impact of eliminating highly-constrained synonymous positions. Preliminary results indicated that their exclusion did not significantly alter the outcomes (data not shown).…”
Section: Methodsmentioning
confidence: 99%